Is the Deliberate Practice View Defensible? A Review of Evidence and Discussion of Issues - Hambrick, David Z.; Macnamara, Brooke N.; Oswald, Frederick L. (Frontiers in Psychology, 2020)
The question of what explains individual differences in expertise within complex domains such as music, games, sports, science, and medicine is currently a major topic of interest in a diverse range of fields, including psychology, education, and sports science, to name just a few. Ericsson and colleagues’ deliberate practice view is highly influential perspective in the literature on expertise and expert performance—but is it viable as a testable scientific theory? Here, reviewing more than 25 years of Ericsson and colleagues’ writings, we document critical inconsistencies in the definition of deliberate practice, along with apparent shifts in the standard for evidence concerning deliberate practice. We also consider the impact of these issues on progress in the field of expertise, focusing on the empirical testability and falsifiability of the deliberate practice view. We then discuss a multifactorial perspective on expertise, and how open science practices can accelerate progress in research guided by this perspective.